If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(0.26 + 9x) = 5.2x (0.26 * 0.5 + 9x * 0.5) = 5.2x (0.13 + 4.5x) = 5.2x Solving 0.13 + 4.5x = 5.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5.2x' to each side of the equation. 0.13 + 4.5x + -5.2x = 5.2x + -5.2x Combine like terms: 4.5x + -5.2x = -0.7x 0.13 + -0.7x = 5.2x + -5.2x Combine like terms: 5.2x + -5.2x = 0.0 0.13 + -0.7x = 0.0 Add '-0.13' to each side of the equation. 0.13 + -0.13 + -0.7x = 0.0 + -0.13 Combine like terms: 0.13 + -0.13 = 0.00 0.00 + -0.7x = 0.0 + -0.13 -0.7x = 0.0 + -0.13 Combine like terms: 0.0 + -0.13 = -0.13 -0.7x = -0.13 Divide each side by '-0.7'. x = 0.1857142857 Simplifying x = 0.1857142857
| p^2-8p=-7 | | y=-5x^3-5x^2+60x | | 4/5g=1/4 | | mx/9=9 | | n^2=6-n | | -2.4x/-1.5= | | 5/7z=2/3 | | 13=x+13 | | 47=5w+12 | | 5(x+1)=2+x | | -382+9x=54x-23 | | x+y+z+a=12.68 | | 7x=-5x+2 | | 9883640/x=100/-0.6 | | 9883640/x=100-0.6 | | (1-x^3)(dy/dx))=3x^y | | -4=6+w | | -8x-2=10x-38 | | 3p=p+34 | | -x+6=-2x-32 | | 42u=252 | | f(x)=cotg(3-2x) | | 3q+6=q+14 | | 26=6x-8 | | 6y-14=16whatisy | | 6x+4y-2x+2y= | | 2-7/3=25 | | 14+3x=6x+133 | | 7(y+1)=3(2y-6) | | Ay=Bx | | 2(3f-9)=8f+10 | | 450-4x=600-7x |